Indigenous dance and dancing Indian : contested representation in the global era - Krystal, Matthew (University of Press of Colorado, 2012)
"Focusing on the enactment of identity in dance, Indigenous Dance and Dancing Indian is a cross-cultural, cross-ethnic, and cross-national comparison of indigenous dance practices